Impact of internal phase volume on the physical, morphological and mechanical characteristics of emulsion templated scaffolds - Aldemir Dikici, Betül (The European Research Journal, 2024)
Objectives: The high porosity of tissue engineering scaffolds is advantageous as they provide a high degree of infiltration of nutrients, enable cell penetration, and support vascularisation. However, the mechanical strength is also critical for providing structural support to the defect site throughout the regeneration process. In this study, we aimed to establish a relationship between internal phase volume and emulsion-templated scaffolds’ physical, morphological and mechanical characteristics. Methods: In this work, tetra methacrylate functionalised polycaprolactone (4PCLMA) polymers were synthesised via ring-opening polymerisation followed by methacrylation. 4PCLMA-based emulsion templated matrices with 60%, 75% and 82% internal phase volumes were fabricated (P60, P75, and P82). These scaffolds’ densities, porosities, average pore and window sizes, degree of interconnectivity values, and mechanical properties were investigated. Results: Increasing internal phase volume reduced the density of the foams by almost two-fold. No direct correlation was observed between average pore size and internal phase volume. Both the average window sizes and the degree of interconnectivity values increase with increasing internal phase volume. Compression modulus values are calculated as 0.46±0.04 MPa, 0.23±0.02 MPa and 0.14±0.01 MPa for P60, P75, and P82, respectively. Increasing internal phase volume from 60% to 82% caused a more than 2-fold reduction in the stiffness of the emulsion-templated matrices. Conclusions: Accordingly, by reporting on this experimental framework, we established a relationship between internal phase volume and the physical, morphological and mechanical characteristics of 4PCMA-based scaffolds to precisely engineer these characteristics for specific tissue engineering applications.